Skin Cancer: Epidemiology, Disease Burden, Pathophysiology, Diagnosis, and Therapeutic Approaches. Issue 1 (January 2017) - Apalla, Zoe; Nashan, Dorothée; Weller, Richard; Castellsagué, Xavier
Abstract Skin cancer, including both melanoma and non-melanoma, is the most common type of malignancy in the Caucasian population. Firstly, we review the evidence for the observed increase in the incidence of skin cancer over recent decades, and investigate whether this is a true increase or an artefact of greater screening and over-diagnosis. Prevention strategies are also discussed. Secondly, we discuss the complexities and challenges encountered when diagnosing and developing treatment strategies for skin cancer. Key case studies are presented that highlight the practic challenges of choosing the most appropriate treatment for patients with skin cancer. Thirdly, we consider the potential risks and benefits of increased sun exposure. However, this is discussed in terms of the possibility that the avoidance of sun exposure in order to reduce the risk of skin cancer may be less important than the reduction in all-cause mortality as a result of the potential benefits of increased exposure to the sun. Finally, we consider common questions on human papillomavirus infection.